The Science of Stories
XX, 280 p.
Keywords: The study of narratives in a variety of disciplines has grown in recent years as a method of better explaining underlying concepts in their respective fields. Through the use of Narrative Policy Framework (NPF), political scientists can analyze the role narrative plays in political discourse.